Faszyzm austriacki (1934–1938) – założenia filozoficzno-ideowe, ustrojowe i praktyka polityczna - Czerwińska-Schupp, Ewa (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
The purpose of this article consists in presentation of Austrian fascism (austrofascism) embodied in the Federal State of Austria 1934–1938. The State represented an important episode in the history of European authoritarianism. In the following paper I address four issues: (1) philosophical, ideological, and doctrinal justification of Austrian fascism, (2) legal and constitutional principles of the regime of Engelbert Dollfuß and Kurt Schuschnigg, (3) relationship between the formal structure of Federal State and the socio-political reality. Finally, (4) I try to answer two interrelated questions concerning the nature of the austrofascist dictatorship and the legitimacy of considering austrofascism as a system of government in the context of phenomenon of fascism.